Second order differential equation

  • Thread starter mr bob
  • Start date
  • #1
38
0
I just came across this one, was going really well until i came across this one.

(d^2y/dx^2) + (dy/dx) = e^(-x)
m^2 + m = 0
m = -1 and m = 0

Now i get the particular integral
Try y = ke^(-x)
(dy/dx) = -ke^(-k)
(d^2y/dx^2) = ke^(-x)


ke^(-x) - ke^(-x) = e^(-x)

I get stuck here as k-k= 0, not one.

Any help would be greatly appreciated.
 

Answers and Replies

  • #2
338
11
mr bob said:
I just came across this one, was going really well until i came across this one.

(d^2y/dx^2) + (dy/dx) = e^(-x)
m^2 + m = 0
m = -1 and m = 0

Now i get the particular integral
Try y = ke^(-x)
(dy/dx) = -ke^(-k)
(d^2y/dx^2) = ke^(-x)


ke^(-x) - ke^(-x) = e^(-x)

I get stuck here as k-k= 0, not one.

Any help would be greatly appreciated.

Try [tex]y=axe^{-x} +be^{-x}[/tex]

-Dan
 
Last edited:

Related Threads on Second order differential equation

  • Last Post
Replies
1
Views
511
  • Last Post
Replies
3
Views
1K
  • Last Post
Replies
10
Views
2K
  • Last Post
Replies
1
Views
1K
  • Last Post
Replies
3
Views
1K
  • Last Post
Replies
1
Views
750
  • Last Post
Replies
5
Views
3K
  • Last Post
Replies
1
Views
852
  • Last Post
Replies
5
Views
943
  • Last Post
Replies
2
Views
1K
Top